Answer:
a) eight and seven ninths minus three and four sixths
Step-by-step explanation:
The required result is ![5\frac{6}{54}](https://tex.z-dn.net/?f=5%5Cfrac%7B6%7D%7B54%7D)
a)
![8\frac{7}{9} -3\frac{4}{6}\\\\=\frac{79}{9} -\frac{22}{6} \\\\Simplifying\ the\ expression:\\\\=\frac{474-198}{54} \\\\=\frac{276}{54}\\\\=5\frac{6}{54}](https://tex.z-dn.net/?f=8%5Cfrac%7B7%7D%7B9%7D%20-3%5Cfrac%7B4%7D%7B6%7D%5C%5C%5C%5C%3D%5Cfrac%7B79%7D%7B9%7D%20%20-%5Cfrac%7B22%7D%7B6%7D%20%5C%5C%5C%5CSimplifying%5C%20the%5C%20expression%3A%5C%5C%5C%5C%3D%5Cfrac%7B474-198%7D%7B54%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B276%7D%7B54%7D%5C%5C%5C%5C%3D5%5Cfrac%7B6%7D%7B54%7D)
b)
![6\frac{8}{9} -1\frac{5}{6}\\\\=\frac{62}{9} -\frac{11}{6} \\\\Simplifying\ the\ expression:\\\\=\frac{372-99}{54} \\\\=\frac{273}{54}\\\\=5\frac{3}{54}](https://tex.z-dn.net/?f=6%5Cfrac%7B8%7D%7B9%7D%20-1%5Cfrac%7B5%7D%7B6%7D%5C%5C%5C%5C%3D%5Cfrac%7B62%7D%7B9%7D%20%20-%5Cfrac%7B11%7D%7B6%7D%20%5C%5C%5C%5CSimplifying%5C%20the%5C%20expression%3A%5C%5C%5C%5C%3D%5Cfrac%7B372-99%7D%7B54%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B273%7D%7B54%7D%5C%5C%5C%5C%3D5%5Cfrac%7B3%7D%7B54%7D)
c)
![4\frac{1}{6} +1\frac{1}{9}\\\\=\frac{10}{9} +\frac{25}{6} \\\\Simplifying\ the\ expression:\\\\=\frac{60+225}{54} \\\\=\frac{285}{54}\\\\=5\frac{15 }{54}](https://tex.z-dn.net/?f=4%5Cfrac%7B1%7D%7B6%7D%20%2B1%5Cfrac%7B1%7D%7B9%7D%5C%5C%5C%5C%3D%5Cfrac%7B10%7D%7B9%7D%20%20%2B%5Cfrac%7B25%7D%7B6%7D%20%5C%5C%5C%5CSimplifying%5C%20the%5C%20expression%3A%5C%5C%5C%5C%3D%5Cfrac%7B60%2B225%7D%7B54%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B285%7D%7B54%7D%5C%5C%5C%5C%3D5%5Cfrac%7B15%20%7D%7B54%7D)
d)
![3\frac{3}{6} +2\frac{4}{9}\\\\=\frac{22}{9} +\frac{21}{6} \\\\Simplifying\ the\ expression:\\\\=\frac{132+189}{54} \\\\=\frac{321}{54}\\\\=5\frac{51 }{54}](https://tex.z-dn.net/?f=3%5Cfrac%7B3%7D%7B6%7D%20%2B2%5Cfrac%7B4%7D%7B9%7D%5C%5C%5C%5C%3D%5Cfrac%7B22%7D%7B9%7D%20%20%2B%5Cfrac%7B21%7D%7B6%7D%20%5C%5C%5C%5CSimplifying%5C%20the%5C%20expression%3A%5C%5C%5C%5C%3D%5Cfrac%7B132%2B189%7D%7B54%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B321%7D%7B54%7D%5C%5C%5C%5C%3D5%5Cfrac%7B51%20%7D%7B54%7D)
![\(\begin{matrix} y=ln(x+3)\\ e^y=x+3\\ e^y-3=x\\ swap ~x~and~y\\ \huge\underline{y=e^x-3}} \end{matrix}\) ](https://tex.z-dn.net/?f=%5C%28%5Cbegin%7Bmatrix%7D%0Ay%3Dln%28x%2B3%29%5C%5C%0Ae%5Ey%3Dx%2B3%5C%5C%0Ae%5Ey-3%3Dx%5C%5C%0Aswap%20~x~and~y%5C%5C%0A%20%5Chuge%5Cunderline%7By%3De%5Ex-3%7D%7D%0A%20%5Cend%7Bmatrix%7D%5C%29%0A)
To get the inverse
of any function f(x) [ just make sure that it passes the horizontal line test]
follow the steps:
- Solve for x, i.e separate x in one side
and the other terms in the other side, included f(x).
- Swap x and f(x).
- The result is the inverse of the original
function
.
-------------------------
Apply that on your function
Answer:
63 sq ft
Step-by-step explanation:
The formula for the area of a trapezoid is
A = h(a + b)/2 where a and b are the lengths of the parallel sides and h is the distance between them
A = 7(11 + 7)/2
= 7(18)/2
= 63 sq ft
It’s -3/2 :) Hope this helps!